PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN PRODUK SAYUR DI GREENHOUSE DEWAPONIK - Widura, Satriya Abiyyu Hibatullah; Maharani, Artita Devi; Stefani, Eska (Fakultas Pertanian UST, 2025)
This study aims to determine the effect of product quality on consumer satisfaction through vegetable product purchasing decisions. Greenhouse Dewaponik is located in Rejowinangun, Kotagede, Yogyakarta. Samples were taken by purposive sampling of 100 consumers who visited and bought Dewaponik products which were then analyzed using path analysis. The results of the analysis stated that product quality had a direct and significant effect on consumer satisfaction. Product quality had a direct and significant effect on purchasing decisions. Furthermore, purchasing decisions had a direct and significant effect on consumer satisfaction. However, product quality had an indirect and significant effect on consumer satisfaction with purchasing decisions as an intervening variable. Meanwhile, together, product quality had an indirect and significant effect on consumer satisfaction with purchasing decisions as an intervening variable. The results of the path analysis of product quality had an indirect effect on consumer satisfaction through purchasing decisions or purchasing decisions could be an intervening variable for product quality and consumer satisfaction.